Influence of beetroot (Beta vulgaris var. cruenta) on mice leukocytes increase - Amaro, Jony (2014)
Background: Beetroot is a flavonoid-containing Mediterranean plant used for food and medicinal purposes. Objectives: To determine the influence of Beta vulgaris var. cruenta extract consumption in increasing albino mice leukocytes. Design: Experimental study. Setting: School N° 1182 bioterium. Biologic material: Twenty male Balb/c albino mice weighing 24 g average. Interventions: Two groups of ten mice each were formed; the experimental group received Beta vulgaris var. cruenta extract at 250 mg/kg oral doses, 2 mL volume every five hours for one week, alternating with nutrients; the control group received nutrients only. Main outcome measures: Leukocyte count. Results: During the conditioning period a slight increase in leukocytes in the control group (3 681 + 431.1) was found compared to the experimental group (3 579 + 473.5), but the difference was not significant. After administering Beta vulgaris var. cruenta extract alternating with nutrient media to the experimental group a significant difference in leukocytes (7 961 + 275,4) was observed when compared with the control group (3 693 + 414,7) (t student p<0,05). Conclusions: In experimental conditions, the consumption of Beta vulgaris var. cruenta extract significantly increased the number of leukocytes.